Potensi Pendapatan Retribusi Parkir: Dari Sudut Pandang Juru Parkir Liar - Muhammad Rizal; Vita Fitria Sari; Charoline Cheisiviyanny; Mayar Afriyenti; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2023)
This research is based on the loss of parking retribution which is quite large in the city of Padang. The purpose of this research is to see the potential retribution generated and the fairness received by parking attendants for parking activities in Padang City, especially in West Padang District. The type of research conducted is descriptive qualitative exploratory. This research method uses primary data and uses observation, interview and documentation techniques in collecting research data. Data analysis in this study using data triangulation. The sample in this study was a parking attendant in West Padang District. The results of this study found that West Padang District has the potential for parking fees of 44% of the set target, if all income and deposits are given to the Padang City Parking Unit. In this study also found that not all parking attendants feel fair with the income they receive.